PARTISIPASI MASYARAKAT DALAM MENCEGAH KEBAKARAN HUTAN DAN LAHAN DI DESA RASAU JAYA II KABUPATEN KUBU RAYA - Nigrum, Nopita Rahmah; Roslinda, Emi; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2019)
Rasau Jaya Village, Kubu Raya district, which detected high hotspots annually. To prevent forest and land fires, community participation is needed.  The purpose of this study was to analyze community participation in preventing forest and land fires, and to find out factors related to community participation in preventing forest and land fires.  The method used in this study is a survey method with data collection techniques in the field using questionnaires and interview techniques.  The number of respondents in this study was 116 people from a population of 851 families. Data analysis used the Kendall Tau Correlation Non parametric statistical test.  The results of research on community participation in preventing forest and land fires show the level of community participation at a moderate level, this is influenced by a close relationship between knowledge and understanding of the functions and benefits of preventing forest and land fires, knowledge can encourage people to take the initiative prevention with socialization and planning activities carried out by the local government. In the ladder of community participation according to Arnstein, Rasau Jaya II village is at the level of Therapy, which is a level of improvement, where there is no real participation, in this case the community is directly involved in a program, but community involvement is not based on a strong mental drive and participation that contributes to the program.Keywords: Forest and land fires, Participation, Rasau Jaya, West Kalimantan